Tourism Public Policies in Brazil (2003-2011): between Neoliberalism and Neodevelopmentalism - Larissa Prado Rodrigues; Cristiane Alcantara de Jesus Santos; Antonio Carlos Campos (Via@)
Neoliberal policies in Brazil were introduced in the political-economic scenario from the 1990s onwards, inciting a late neoliberalization process in the country comparing to Latin American scenario. In 2003, despite a so-called left-wing government having been elected in the country, neoliberal policies continued to perpetuate themselves on the economic agenda; coexisting contradictorily with a series of social policies adopted, revealing the tendency of Lula governments to the alleged "neodevelopmentalism". Therefore, this research aims to analyse the national plans and programs aimed at the development of tourism activity, elaborated by the Ministry of Tourism, in the light of a supposed propagation and reproduction of neoliberal and neodevelopmentalism tendencies. Methodologically, the analysis was carried out through bibliographic and documentary research in official agencies. It is concluded that these paradigms were present during the Lula da Silva government (2003-2011), guiding plans and programs aimed at the development of Brazilian tourism.